Mild hydrostatic pressure triggers oxidative responses in Escherichia coli. - Aurelie Guyet; Martyn Dade-Robertson; Anil Wipat; John Casement; Wendy Smith; Helen Mitrani; Meng Zhang (PLoS ONE, 2018)
Hydrostatic pressure is an important physical stimulus which can cause various responses in bacterial cells. The survival and cellular processes of Escherichia coli under hydrostatic pressures between 10 MPa and 110 MPa have been studied. However, understanding bacterial responses to moderately elevated pressure of up to 10 MPa is useful for a range of different applications including for example in smart and responsive materials. In this study, the genetic responses of E. coli K-12 MG1655 to 1 MPa pressure was examined using transcriptomic analysis by RNA-Seq. The results show that 101 genes were differentially expressed under 1 MPa pressure in E. coli cells, with 85 of them up-regulated. The analysis suggested that some genes were over expressed to adapt the increase of oxygen levels in our system, and several functional categories are involved including oxidative stress responses, Fe-S cluster assembly and iron acquisition. Two differentially expressed genes azuC and entC were further investigated using RT-qPCR, and GFP reported strains of those two genes were created, AG1319 (PazuC azuC-msfgfp) and AG1321 (PentC entC-msfgfp). A linear response of azuC expression was observed between 0 MPa to 1 MPa by monitoring the fluorescence signal of strain AG1319 (PazuC azuC-msfgfp). This study is the first report to demonstrate the genetic response of bacterial cells under 1 MPa hydrostatic pressure, and provides preliminary data for creating pressure sensing bacterial strains for a wide range of applications.